Constitutional Protection of the Right to Work (A Comparative Analytical Study) - الشريفي, صفاء محمد; الاسدي, جمانة جاسم (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The right to work is what a person has the power to exercise his humanity, in a manner that is compatible with his physical and intellectual potential and his academic qualifications, to the extent that guarantees him a well-off life, or that the state guarantees to a person the right to protection and equality before undertaking general government work or what is in a private company or cooperative institution , and other places of work, so that the worker economically secures what he feels self-esteem, dignity, and reassurance about his present and future, and from here the importance of the study emerges in highlighting the constitutional protection provided by the constitutional judiciary for the right to work for citizens. In terms of the protection of the constitutional judiciary for rights and freedoms in general and the rights contained in its document in particular, it was necessary to highlight the right to work as one of the basic rights close to the right to life, rather it is a constitutional principle in itself, based on Article 22 of the Iraqi constitution in force for the year 2005 AD Which states: "First - Work is a right for all Iraqis in a way that guarantees them a decent life." However, what is happening on the ground is the lack of responsibility of the state in providing this right, and the failure of its supervisory and judicial agencies to protect the right to work, which constituted the occurrence of cases of disguised unemployment and the accumulation of employment. Expatriate without deterrence and legal justification. Based on that, we raise several questions about the role of the constitutional judiciary and the position of the Federal Supreme Court in Iraq in protecting the right to work, and the effectiveness of Iraqi Labor Law No. 37 of 2015 AD in protecting this right in practice, in addition to reviewing the positions of the Federal Supreme Court in Turkey, which we will take as a place for comparison in this research. Which we will prepare according to the analytical and comparative approaches between the two constitutions of Iraq and its Turkish counterpart, in a serious attempt to find constitutional ways that provide absolute protection for this right as a constitutional principle that cannot be overlooked and its outputs. The research also aims to stand on the elements provided by the Ministry of Labor and Social Affairs to prevent and reduce The phenomenon of unemployment and the inequity of those with university degrees in obtaining appropriate work in government departments and private institutions. Accordingly, we decided to research according to dividing it bilaterally and into two sections. In the first section, we review the concept of the right to work and divide it into two demands. The first requirement is the definition of the right to work, and the second requirement is the legal basis for the right to work. As for the second topic, we will discuss the role of the constitutional judiciary and divide it into two demands. The first requirement is the position of the Federal Court. Supreme Court in Iraq The second requirement is the position of the Federal Supreme Court in Turkey.